ANALISIS AKULTURASI BUDAYA ETNIS JAWA DENGAN MADURA DI DUSUN PENDAMAR KECAMATAN TELUK PAKEDAI - Manja, Nur Sri; Imran, Imran; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research discusses cultural acculturation between two ethnic groups and specifically discusses acculturation on the aspect of livelihood, social system, and language system. This study aims to find out and describe the cultural acculturation between Javanese and Madurese in Pendamar village of TelukPakedai District. This is qualitative research, of which the discussion was presented descriptively. The data were collected using observation, interviews, and documentation techniques. The findings showed that cultural acculturation in the aspect of livelihood was shown by the community who previously worked as farmers, changed to become oil palm workers due to the entry of oil palm companies. They also continue to work as farmers cultivating their fields to plant rice, corn, vegetables, and coconut trees. cultural acculturation in the aspect of the kinship system was shown through all the two ethnicities which previously each followed a single kinship system, transformed into following the kinship system of the two joint ethnic groups. Besides, there are descendants of ethnic Javanese with Madurese who follow the principles of patrilineal descent and bilinear descent. Acculturation in the aspect of language was shown that both ethnics can communicate using Indonesian, Javanese, and Madurese.Keywords: Cultural Acculturation, Javanese, Maduranese